The Effect of Hydroxyurea on Vasculopathy in a Child with Sickle Cell Disease - Helton, Kathleen J.; Wang, Winfred C.; Wynn, Lynn W.; Khan, Raja B.; Steen, R. Grant (American Journal of Neuroradiology, 2002)
Summary: We report serial CNS findings in a girl with sickle cell disease and stroke. Religious considerations precluded transfusion and bone marrow transplantation; therefore, she received single-agent hydroxyurea therapy for almost 6 years. MR angiography showed that vascular patency improved, although diffuse cerebral atrophy slowly worsened. Hydroxyurea can be effective in treating vasculopathy, but it might not prevent the progression of parenchymal damage in advanced disease.